5‐HT2B receptor antagonists attenuate myofibroblast differentiation and subsequent fibrotic responses in vitro and in vivo. Issue 15 (1st August 2016) - Löfdahl, Anna; Rydell‐Törmänen, Kristina; Müller, Catharina; Martina Holst, C.; Thiman, Lena; Ekström, Gunilla; Wenglén, Christina; Larsson‐Callerfelt, Anna‐Karin; Westergren‐Thorsson, Gunilla
Abstract: Pulmonary fibrosis is characterized by excessive accumulation of connective tissue, along with activated extracellular matrix (ECM)‐producing cells, myofibroblasts. The pathological mechanisms are not well known, however serotonin (5‐HT) and 5‐HT class 2 (5‐HT2 ) receptors have been associated with fibrosis. The aim of the present study was to investigate the role of 5‐HT2B receptors in fibrosis, using small molecular 5‐HT2B receptor antagonists EXT5 and EXT9, with slightly different receptor affinity. Myofibroblast differentiation [production of alpha‐smooth muscle actin ( α ‐SMA)] and ECM synthesis were quantified in vitro, and the effects of the receptor antagonists were evaluated. Pulmonary fibrosis was also modeled in mice by subcutaneous bleomycin administrations (under light isoflurane anesthesia), and the effects of receptor antagonists on tissue density, collagen‐producing cells, myofibroblasts and decorin expression were investigated. In addition, cytokine expression was analyzed in serum. Lung fibroblasts displayed an increased α ‐SMA ( P  < 0.05) and total proteoglycan production ( P  < 0.01) when cultured with TGF‐ β 1 together with 5‐HT, which were significantly reduced with both receptor antagonists. Following treatment with EXT5 or EXT9, tissue density, expression of decorin, number of collagen‐producing cells, and myofibroblasts were significantly decreased in vivo compared to bleomycin‐treated mice. Receptor antagonization also significantly reduced systemic levels of TNF‐ α and IL‐1 β, indicating a role in systemic inflammation. In conclusion, 5‐HT2B receptor antagonists have potential to prevent myofibroblast differentiation, in vitro and in vivo, with subsequent effect on matrix deposition. The attenuating effects of 5‐HT2B receptor antagonists on fibrotic tissue remodeling suggest these receptors as novel targets for the treatment of pulmonary fibrosis. Abstract : 5‐HT2B receptor antagonists have potential to prevent myofibroblast differentiation, in vitro and in vivo, with subsequent effect on matrix deposition, suggesting 5‐HT2B receptors as novel targets for the treatment of pulmonary fibrosis.